Citizen Science on Social Media: One Medical Librarian's Experience of Launching and Maintaining a Moderated Facebook Citizen Science Discussion Group (www.Facebook.com/groups/BiomeReconstitution). Issue 1 (2nd January 2016) - Beales, Donna L.
ABSTRACT: Health information available on the World Wide Web varies in quality, and consumers are deluged with sources offering questionable health practices. This concern is not new to medical librarians. Consumers actively seeking health information for their medical conditions seem to be migrating to social media sites to gain knowledge. These sites appear to be a promising new platform for medical librarians to disseminate quality information.